Intervensi Lean Six Sigma Menurunkan Waktu Tunggu Pelayanan Obat Pasien Jkn di Depo Farmasi Rawat Jalan RS Ari Canti Bali - Made Putri Widyantini; Purwadhi Purwadhi; Maxsi Ary (Lembaga Pengembangan Kinerja Dosen, 2026)
Long medication waiting times in outpatient pharmacy services can hinder therapy continuity and reduce patient trust, particularly among National Health Insurance (JKN) patients who make up the majority of visits at RS Ari Canti Bali. Despite several improvement efforts, the hospital's waiting-time quality indicator remained below the minimum service standard target. This study aimed to identify the root causes of delay and to apply a Lean Six Sigma intervention through the Define-Measure-Analyze-Improve-Control (DMAIC) framework to reduce medication waiting time for JKN patients at the outpatient pharmacy unit, as well as to design and evaluate a revised standard operating procedure to sustain the improvement. A mixed-methods case study design was used, combining in-depth interviews, observation, document review, and time studies analyzed with Value Stream Mapping, fishbone diagrams, and the 5-Why technique. Waiting-time data were collected from 30 baseline prescriptions and 30 post-intervention prescriptions and compared using a paired sample t-test. Results showed that average waiting time decreased from 27.33 to 16.93 minutes, a reduction of about 38 percent, with the largest decrease found in compounded prescriptions. The paired sample t-test confirmed that the reduction was statistically significant. These findings imply that an integrated Lean Six Sigma approach, supported by a sustainable standard operating procedure and monitoring plan, can meaningfully improve pharmacy service quality and help hospitals meet national waiting-time standards for JKN patients.